Forming packaging materials

The packaging material with a heat-resistant resin layer and specific adhesive composition addresses peeling and cracking issues, ensuring durable and uniform coloring for battery cases under harsh conditions.

JP7610961B2Active Publication Date: 2025-01-09LISSENOK PACKAGING CO LTD
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
JP2020199974
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-01-10
Filing Date
2020-12-02
Publication Date
2025-01-09
Estimated Expiration
2040-12-02

AI Technical Summary

Technical Problem

Existing packaging materials for batteries, particularly those colored black, suffer from peeling and cracking issues due to the use of carbon black-containing printed layers, especially under harsh conditions like high temperature and humidity, affecting uniform coloring and durability.

Method used

A packaging material comprising a heat-resistant resin layer, a thermoplastic resin layer, a metal foil layer, and adhesive layers with a specific composition of a two-component curable polyester urethane resin, ensuring strong bonding and resistance to peeling, even under harsh conditions.

Benefits of technology

The material maintains uniform coloring and prevents peeling of the resin layer, providing excellent heat resistance, moldability, and corrosion resistance, suitable for forming battery cases.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007610961000002
    Figure 0007610961000002
  • Figure 0007610961000003
    Figure 0007610961000003
  • Figure 0007610961000004
    Figure 0007610961000004
Patent Text Reader

Abstract

To prevent delamination of a packaging material for molding with a coloring layer.SOLUTION: In a packaging material 1 for molding which includes heat-resistant resin layer 2 as an outer layer, a thermoplastic resin layer 3 as an inner layer, a metal foil layer 4 provided between these two layers, a first adhesive layer 5 provided between the metal foil layer 4 and the heat-resistant resin layer 2, and a second adhesive layer 6 provided between the metal foil layer 4 and the thermoplastic resin layer 3, the first adhesive layer 5 comprises a coloring adhesive composition containing a coloring pigment and an adhesive, the coloring adhesive composition contains the coloring pigment of 2 mass% or more and less than 5 mass% with respect to a solid component, the first adhesive layer 5 is coated with the coloring adhesive composition of 5 g / m2 to 10 g / m2, and the first adhesive layer 5 contains the coloring pigment of 0.25 g / m2 to 0.49 g / m2.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a moldable packaging material that is suitably used, for example, as a case for a notebook computer, a mobile phone, an in-vehicle battery, or a stationary secondary battery (lithium ion secondary battery), and also as a packaging material for food and medicine. [Background technology]

[0002] There is an increasing demand for batteries such as lithium ion secondary batteries to be colored in order to match the appearance and color of the electrical equipment, etc., in which they are to be installed. For example, devices are often colored black to give them a sense of dignity and luxury, and in such cases, batteries are often also colored black.

[0003] This type of packaging material is generally a laminate in which a resin layer is laminated on both sides of a metal foil, and to color the battery black or other colors, there are various means, such as coloring the resin layer used in the packaging material, providing a printed layer under the base resin layer, coloring the adhesive layer between the base resin layer and the shielding metal layer, and, when the base resin layer is composed of multiple layers, coloring the adhesive layer between the layers.

[0004] For example, there are cases in which a layer containing an identification mark is provided in any of the substrate layer (resin layer), adhesive layer, or metal foil layer of a battery packaging material, and in some cases, the entire packaging material can be colored by coloring a printed layer provided under the substrate layer or the adhesive layer of the substrate layer (see Patent Documents 1 and 2).

[0005] Also, there is a battery packaging material having a black body material layer between a metal foil layer and an outer film layer to promote heat dissipation (see Patent Document 3). [Prior art documents] [Patent documents]

[0006] [Patent Document 1] International Publication WO 2011 / 016506 A1 [Patent Document 2] JP 2011-054563 A [Patent Document 3] JP 2011-096552 A Summary of the Invention [Problem to be solved by the invention]

[0007] When the above-mentioned packaging material is colored black, it is common to provide a printed layer using printing ink containing a pigment such as carbon black.

[0008] However, when a printed layer containing carbon black as a pigment is provided on the inner surface of the outer resin layer constituting the moldable packaging material in order to color the battery black, the following problems arise.

[0009] In other words, when the above black packaging material is formed into a container (case) shape by deep drawing or stretch molding, the carbon black-containing printed layer partially cracks and peels off, revealing the underlying layer (which is not black), thereby compromising the uniform black coloring.

[0010] Such partial peeling of the printed layer also occurs when the black packaging material is sealed after the electrodes and electrolyte are enclosed, or when a battery packaged in the black packaging material is used in a somewhat harsh environment such as high temperature and humidity.

[0011] Moreover, the same problem occurs not only in black packaging materials using carbon black, but also in packaging materials colored with other pigments.

[0012] Furthermore, in recent years, batteries such as lithium ion secondary batteries have become increasingly high-capacity, and packaging materials are now required to have even higher properties, such as high moldability, heat resistance, and resistance to moist heat. [Means for solving the problem]

[0013] The present invention has been made in consideration of the above technical background, and aims to provide a molding packaging material in which the colored layer does not partially crack and peel off during molding and sealing, and even when used in a somewhat severe environment such as high temperature and humidity.

[0014] That is, the present invention has the configurations described in [1] to

[10] .

[0015] [1] A molding packaging material comprising a heat-resistant resin layer as an outer layer, a thermoplastic resin layer as an inner layer, a metal foil layer disposed between these two layers, a first adhesive layer disposed between the metal foil layer and the heat-resistant resin layer, and a second adhesive layer disposed between the metal foil layer and the thermoplastic resin layer, The first adhesive layer is made of a colored adhesive composition containing a color pigment and an adhesive, the colored adhesive composition containing 2% by mass or more and less than 5% by mass of the color pigment based on the solid content, and the first adhesive layer has a thickness of 5 g / m 2 ~10g / m 2 The colored adhesive composition is applied to the first adhesive layer, and the first adhesive layer has a thickness of 0.25 g / m 2 ~0.49g / m 2 A moldable packaging material comprising a color pigment as defined above.

[0016] [2] The molded packaging material according to item 1, wherein the adhesive in the colored adhesive composition contains a two-component curing type polyester urethane resin made of a polyester resin as a base resin and a polyfunctional isocyanate compound as a curing agent, the polyester resin having a number average molecular weight (Mn) of 8,000 to 25,000 and a weight average molecular weight (Mw) of 15,000 to 50,000, with a ratio thereof (Mw / Mn) of 1.3 to 2.5, and the polyfunctional isocyanate compound containing 50 mol % or more of an aromatic isocyanate.

[0017] [3] In the two-component curing polyester urethane resin, the polyester resin as a main component is made from dicarboxylic acid and dialcohol as raw materials; 3. The moldable packaging material according to item 2, wherein the dicarboxylic acid includes an aliphatic dicarboxylic acid having an even number of methylene units in the methylene chain and an aromatic dicarboxylic acid, and the content of the aromatic dicarboxylic acid in the total amount of the dicarboxylic acids is 40 to 80 mol %.

[0018] [4] The molding packaging material according to item 2 or 3 above, wherein the cured film of the two-component curing polyester urethane resin has a Young's modulus of 70 to 400 MPa as determined by a tensile test (JIS K7162).

[0019] [5] The moldable packaging material according to any one of items 1 to 4 above, wherein the first adhesive layer has a thickness of 4.5 μm to 10 μm.

[0020] [6] The moldable packaging material according to any one of items 1 to 5 above, having a chemical conversion coating on at least one surface of the metal foil layer.

[0021] [7] The molding packaging material according to any one of items 1 to 6, wherein the heat-resistant resin layer is made of a stretched film having a hot water shrinkage rate of 2% to 20%.

[0022] [8] The molding packaging material according to any one of items 1 to 7 above, further comprising a matte coating layer on an outer surface of the heat-resistant resin layer.

[0023] [9] A molded case obtained by deep drawing or stretch molding the moldable packaging material according to any one of items 1 to 8 above.

[0024]

[10] The molded case according to item 9 above, which is used as a battery case. Effect of the Invention

[0025] The molding packaging material described in [1] above is colored by the first adhesive layer on the outer surface side of the molding packaging material. The color pigment is specified by the concentration in the colored adhesive composition, the coating amount of the colored adhesive composition, and the content of the color pigment in the first adhesive layer, so that the first adhesive layer does not become brittle due to the colored pigment while maintaining uniform and sufficient coloring, and the bonding strength between the heat-resistant resin layer and the metal foil layer is not reduced. Therefore, when the packaging material is subjected to molding such as deep drawing and stretch molding, or when the packaging material is sealed for sealing, the heat-resistant resin layer does not peel off. In addition, even when used in a somewhat harsh environment such as high temperature and humidity, the heat-resistant resin layer does not peel off.

[0026] The molded packaging material described in [2] above uses an adhesive containing a specific two-component curing polyester urethane resin, which gives the adhesive coating suitable strength, elongation, and excellent heat resistance, and further allows a balance to be maintained between adhesive application suitability (broad molecular weight distribution) and performance (narrow molecular weight distribution).

[0027] The molding packaging materials described in the above items [3] and [4] are particularly effective in preventing peeling between the heat-resistant resin layer and the metal foil layer.

[0028] The molding packaging material described in [5] above has a film thickness of the first adhesive layer set to 4.5 μm to 10 μm, which is sufficient to conceal the metallic luster of the metal foil layer and also suppresses curling, making it easy to handle during molding processing.

[0029] In the molded packaging material described in [6] above, the metal foil layer has a chemical conversion coating on its surface, which prevents peeling of the adhesive while also preventing corrosion of the metal foil, thereby providing a molded packaging material with high corrosion resistance.

[0030] The moldable packaging material described in [7] above can achieve high moldability by setting the hot water shrinkage rate to 2% to 20%.

[0031] The moldable packaging material described in [8] above has excellent moldability because a matte coating layer is formed on the outer surface of the heat-resistant resin layer.

[0032] The molded case described in [9] above provides a molded case in which the heat-resistant resin layer does not peel off, not only when it is sealed, but also when it is used in a somewhat severe environment such as high temperature and humidity.

[0033] The molded case described in

[10] above provides a battery case in which the heat-resistant resin layer does not crack or peel off partially, not only during sealing but also when used in a somewhat severe environment such as high temperature and humidity. [Brief description of the drawings]

[0034] [Figure 1] 1 is a cross-sectional view showing one embodiment of a moldable packaging material according to the present invention. [Diagram 2] FIG. 1 is a SS curve diagram of a cured film of a two-component curing polyester urethane resin adhesive. [Diagram 3] FIG. 4 is a cross-sectional view showing another embodiment of the moldable packaging material according to the present invention. [Figure 4] FIG. 4 is a cross-sectional view showing still another embodiment of the moldable packaging material according to the present invention. [Diagram 5] FIG. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0035] Fig. 1 shows a battery case molding packaging material 1 having a basic laminated structure, which is one embodiment of the present invention. This molding packaging material 1 is used as a material for lithium-ion secondary battery cases. That is, the molding packaging material 1 is used as a secondary battery case by being subjected to molding such as deep drawing.

[0036] The battery case packaging material 1 has a configuration in which a heat-resistant resin layer (outer layer) 2 is laminated integrally onto the upper surface of a metal foil layer 4 via a first adhesive layer 5, and a thermoplastic resin layer (inner layer) 3 is laminated integrally onto the lower surface of the metal foil layer 4 via a second adhesive layer 6.

[0037] Each layer is described in detail below.

[0038] (Heat-resistant resin layer) The heat-resistant resin layer (outer layer) 2 is not particularly limited, but examples thereof include polyamide film, polyester film, etc., and these stretched films are preferably used. Among them, it is particularly preferable to use a biaxially stretched polyamide film, a biaxially stretched polybutylene terephthalate (PBT) film, a biaxially stretched polyethylene terephthalate (PET) film, or a biaxially stretched polyethylene naphthalate (PEN) film as the heat-resistant resin layer 2 in terms of formability and strength. The polyamide film is not particularly limited, but examples thereof include a 6 nylon film, a 6,6 nylon film, and an MXD nylon film. The heat-resistant resin layer 2 may be formed of a single layer, or may be formed of a multilayer structure, such as a PET film / polyamide film. Furthermore, it is preferable that these films are colorless and transparent in consideration of fully expressing the coloring effect of the adhesive.

[0039] The thickness of the heat-resistant resin layer 2 is preferably 9 μm to 50 μm. When a polyester film is used, the thickness is preferably 9 μm to 50 μm, and when a polyamide film is used, the thickness is preferably 10 μm to 50 μm. By setting the thickness to be equal to or greater than the above-mentioned preferable lower limit, sufficient strength as a packaging material can be ensured, and by setting the thickness to be equal to or less than the above-mentioned preferable upper limit, stress during stretch forming or draw forming can be reduced, improving formability.

[0040] Furthermore, the heat-resistant resin layer 2 is preferably a stretched film having a hot water shrinkage rate of 2% to 20%.

[0041] The hot water shrinkage rate is expressed as the rate of dimensional change in the stretching direction of a test piece (10 cm x 10 cm) of the heat-resistant resin layer 2 before and after immersion in hot water at 95°C for 30 minutes, and is calculated by the following formula. Hot water shrinkage rate (%) = {(XY) / X} x 100 X: Dimension in the stretching direction before immersion treatment Y: Dimension in the stretching direction after immersion treatment.

[0042] When a biaxially stretched film is used, the hot water shrinkage rate is the average value of the dimensional change rates in the two stretching directions.

[0043] If the hot water shrinkage is less than 2%, it is difficult to obtain high moldability when performing deep drawing, stretch forming, or other molding. On the other hand, if the hot water shrinkage is more than 20%, the heat-resistant resin layer 2 is easily peeled off from the first adhesive layer 5 when used in a somewhat severe environment such as high temperature and humidity after performing deep drawing, stretch forming, or other molding. In particular, it is preferable to use a stretched film having a hot water shrinkage of 2.5 to 10% as the heat-resistant resin layer 2. Furthermore, it is more preferable to use a stretched film having a hot water shrinkage of 3.0% to 6.0%, and it is particularly preferable to use a stretched film having a hot water shrinkage of 3.5% to 5.0%.

[0044] (thermoplastic resin layer) The thermoplastic resin layer (inner layer) 3 has the function of providing the packaging material with excellent chemical resistance against highly corrosive electrolytes used in lithium ion secondary batteries and the like, and also of imparting heat sealability to the packaging material.

[0045] The thermoplastic resin layer 3 is preferably an unstretched thermoplastic resin film layer, although it is not particularly limited thereto. The thermoplastic resin layer 3 is preferably an unstretched film made of at least one thermoplastic resin selected from the group consisting of polyethylene, polypropylene, olefin copolymers, acid-modified products thereof, and ionomers, from the viewpoints of chemical resistance and heat sealability, although it is not particularly limited thereto.

[0046] The thickness of the thermoplastic resin layer 3 is preferably set to 20 μm to 100 μm. By setting the thickness to 20 μm or more, the occurrence of pinholes can be sufficiently prevented, and by setting the thickness to 100 μm or less, the amount of resin used can be reduced, thereby enabling cost reduction. Among these, the thickness of the thermoplastic resin layer 3 is particularly preferably set to 30 μm to 50 μm. The thermoplastic resin layer 3 may be a single layer or a multilayer. An example of a multilayer film is a three-layer film in which random polypropylene films are laminated on both sides of a block polypropylene film.

[0047] (metal foil layer) The metal foil layer 4 plays a role of imparting gas barrier properties that prevent the intrusion of oxygen and moisture to the moldable packaging material 1. The metal foil layer 4 is not particularly limited, but examples thereof include aluminum foil, copper foil, and stainless steel foil, and aluminum foil is generally used. The thickness of the metal foil layer 4 is preferably 20 μm to 100 μm. When the thickness is 20 μm or more, the occurrence of pinholes during rolling in manufacturing the metal foil can be prevented, and when the thickness is 100 μm or less, the stress during stretch forming or drawing can be reduced, improving formability.

[0048] (First adhesive layer) The first adhesive layer 5 is a layer that bonds the metal foil layer 4 to the heat-resistant resin layer 2, which is the outer layer, and also imparts color (including achromatic color) to the outer surface of the moldable packaging material 1 to conceal the metal foil layer 4.

[0049] The first adhesive layer 5 is made of a colored adhesive composition containing a colored pigment and an adhesive. The present invention specifies the concentration of the colored pigment in the colored adhesive composition and the amount of the colored adhesive composition applied, and further specifies the range of the content of the colored pigment in the first adhesive layer 5 determined by these. By specifying the colored pigment according to these three criteria, it is possible to prevent the hardened first adhesive layer 5 from becoming brittle while obtaining the visual effect of the colored pigment. That is, even if the colored adhesive composition has a low concentration of the colored pigment, the visual effect of the colored pigment can be obtained if the amount of application is sufficient, and since the concentration of the colored pigment in the colored adhesive composition is low, the hardened first adhesive layer 5 does not become brittle and does not reduce the bonding strength between the heat-resistant resin layer 2 and the metal foil layer 4. Therefore, when the packaging material is subjected to molding such as deep drawing and stretch molding, or when the packaging material is sealed for sealing, the heat-resistant resin layer does not peel off. In addition, even when used in a somewhat harsh environment such as high temperature and humidity, the heat-resistant resin layer 2 does not peel off.

[0050] The colored adhesive composition contains a color pigment in an amount of 2% by mass or more and less than 5% by mass of the solid components of the colored adhesive composition. If the content of the color pigment in the colored adhesive composition is less than 2% by mass, the visual effect is poor, whereas if it is 5% by mass or more, the first adhesive layer 5 tends to become hard and brittle, and the adhesive strength to the metal foil layer 4 decreases, making the heat-resistant resin layer 2 prone to peeling. The preferred content of the color pigment is 2.5% to 4.9% by mass.

[0051] The first adhesive layer 5 has a thickness of 5 g / m 2 ~10g / m 2 The colored adhesive composition is applied in an amount of 5 g / m 2 If the coating amount of the colored adhesive composition is less than 10 g / m, the effect of concealing the metallic luster of the metal foil layer 4 is small, and the visual effect of the color pigment is reduced. 2 If the coating amount exceeds 6 g / m, the processability is deteriorated, which leads to an increase in cost. 2 ~10g / m 2 It is.

[0052] In addition, the thickness of the first adhesive layer 5 is preferably in the range of 4.5 μm to 10 μm. If the thickness is less than 4.5 μm, the effect of concealing the metallic luster of the metal foil layer 4 is small. On the other hand, if the thickness exceeds 10 μm, the drying time during the preparation of the moldable packaging material 1 may be long, which may reduce the production efficiency, or the moldable packaging material 1 may curl, which may reduce the handleability during the molding process. The curl is a phenomenon in which the edge of the moldable packaging material 1 bounces up due to the difference in the shrinkage rate of the materials used for the outer layer (heat-resistant resin layer 2) and the inner layer (thermally adhesive resin layer 5) during the aging treatment in the preparation process of the moldable packaging material 1. If the moldable packaging material 1 curls, it becomes difficult to handle it when molding the battery case, the container body, or the lid material. Therefore, by setting the thickness of the first adhesive layer 5 in the range of 4.5 μm to 10 μm, the effect of concealing the metallic luster of the metal foil layer 4 can be sufficiently obtained, and the occurrence of curling can be suppressed to provide a moldable packaging material 1 with good handleability. An especially preferred thickness of the first adhesive layer 5 is 5 μm to 7 μm.

[0053] The first adhesive layer has a thickness of 0.25 g / m 2 ~0.49g / m 2 The content of the color pigment in the first adhesive layer 5 is 0.25 g / m 2 If the density is less than 0.49 g / m, the effect of concealing the metallic luster of the metal foil layer 4 is small and the visual effect of the color pigment is small. 2 Since sufficient visual effect can be obtained, 0.49 g / m 2 A large amount of color pigment exceeding this amount will be wasted. The preferred content of color pigment in the first adhesive layer 5 is 0.25 g / m 2 ~0.3g / m 2 It is.

[0054] In the colored adhesive composition, the type of colored pigment is not limited, and azo pigments, phthalocyanine pigments, condensed polycyclic pigments, inorganic pigments, etc. can be used. Carbon black is recommended as a black pigment. The colored pigment preferably has an average particle size of 0.1 μm to 5 μm, and more preferably has an average particle size of 0.5 μm to 2.5 μm. A pigment dispersing machine is preferably used to disperse the pigment, and a pigment dispersing agent such as a surfactant can also be used to disperse the pigment.

[0055] The type of adhesive in the colored adhesive composition is not limited, but the adhesive must have excellent adhesive strength and moldability, and be capable of suppressing delamination during deep molding. As an adhesive that satisfies such conditions, an adhesive containing a two-component curing polyester urethane resin made of a polyester resin as a base resin and a polyfunctional isocyanate compound as a curing agent is recommended.

[0056] The polyester resin is a copolymer made from polyvalent carboxylic acid and polyhydric alcohol as raw materials, and preferable materials and compositions are as follows.

[0057] It is preferable to use both aliphatic dicarboxylic acids and aromatic dicarboxylic acids as the polyvalent carboxylic acids. In addition, whether the methylene number of the methylene chain of the aliphatic dicarboxylic acid is odd or even is a factor that affects the crystallinity of the resin, and since dicarboxylic acids having an even number of methylenes produce hard resins with high crystallinity, it is preferable to use aliphatic dicarboxylic acids having an even number of methylenes. Examples of aliphatic dicarboxylic acids having an even number of methylenes include succinic acid (2 methylenes), adipic acid (4 methylenes), suberic acid (6 methylenes), and sebacic acid (8 methylenes).

[0058] Examples of aromatic dicarboxylic acids include isophthalic acid, terephthalic acid, naphthalenedicarboxylic acid, and phthalic anhydride.

[0059] In addition, by setting the content of aromatic dicarboxylic acid to the total amount of aliphatic dicarboxylic acid and aromatic dicarboxylic acid in the range of 40 to 80 mol%, in other words, by limiting the content of aliphatic dicarboxylic acid to the range of 20 to 60 mol%, a resin with high adhesive strength and good moldability can be produced, which can be molded into a case with good moldability and high sidewalls, and can suppress delamination between the metal foil layer 4 and the heat-resistant resin layer 2. In addition, if the content of aromatic dicarboxylic acid is less than 40 mol%, the film properties are reduced and cohesive delamination is likely to occur, making delamination more likely to occur. On the other hand, if the content of aromatic dicarboxylic acid exceeds 80%, the resin tends to harden and adhesion performance tends to decrease. A particularly preferred content of aromatic dicarboxylic acid is 50 to 70 mol%.

[0060] Examples of the polyhydric alcohol include ethylene glycol, propylene glycol, 1,3-butanediol, 1,4-butanediol, diethylene glycol, dipropylene glycol, neopentyl glycol, 1,5-pentanediol, 1,6-hexanediol, octanediol, 1,4-cyclohexanediol, and 2-butyl-2-ethyl-1,3-propanediol.

[0061] The molecular weight of the polyester resin is specified as a number average molecular weight (Mn) of 8,000 to 25,000 and a weight average molecular weight (Mw) of 15,000 to 50,000, and the ratio (Mw / Mn) of these is 1.3 to 2.5. The number average molecular weight (Mn) is 8,000 or more and the weight average molecular weight (Mw) is 15,000 or more to obtain suitable coating film strength and heat resistance, and the number average molecular weight (Mn) is 25,000 or less and the weight average molecular weight (Mw) is 50,000 or less to obtain suitable coating film elongation without being too hard. In addition, the ratio (Mw / Mn) of these is 1.3 to 2.5 to obtain a suitable molecular weight distribution, and a balance between adhesive application suitability (wide distribution) and performance (narrow distribution) can be maintained. The polyester resin has a particularly preferred number average molecular weight (Mn) of 10,000 to 23,000, a particularly preferred weight average molecular weight (Mw) of 20,000 to 40,000, and a particularly preferred (Mw / Mn) of 1.5 to 2.3.

[0062] The molecular weight of the polyester resin can be adjusted by chain extension with a polyfunctional isocyanate. That is, when the polyester component in the base resin is linked with NCO, a polymer with a terminal hydroxyl group is generated, and the molecular weight of the polyester resin can be adjusted by adjusting the equivalent ratio between the isocyanate group and the hydroxyl group of the polyester. In the present invention, it is preferable to use one linked so that the equivalent ratio (OH / NCO) is 1.01 to 10. Another molecular weight adjustment method can be changing the reaction conditions of the polycondensation reaction of a polycarboxylic acid and a polyhydric alcohol (adjusting the blending molar ratio of the polycarboxylic acid and the polyhydric alcohol).

[0063] Furthermore, an epoxy resin or an acrylic resin may be added as an additive to the adhesive base.

[0064] The polyfunctional isocyanate compound as the curing agent may be any of various aromatic, aliphatic, and alicyclic isocyanate compounds. Specific examples include polyfunctional isocyanate modified products of one or more of aliphatic diisocyanates such as hexamethylene diisocyanate (HDI), isophorone diisocyanate (IPDI), aromatic tolylene diisocyanate (TDI), and diphenylmethane diisocyanate (MDI). As a modification method, in addition to adducts with polyfunctional active hydrogen compounds such as water, glycerin, and trimethylolpropane, polyfunctional isocyanate modified products obtained by polymerization reactions such as isocyanuration, carbodiimide, and polymerization may be used, and one or more of these may be mixed and used. However, in order to increase the adhesive strength after curing and obtain the effect of preventing peeling of the heat-resistant resin layer 2, it is preferable that the aromatic isocyanate compound is contained in an amount of 50 mol% or more. The content of the aromatic isocyanate compound is particularly preferably 70 mol% or more.

[0065] In the two-component curing polyester urethane resin, the blending ratio of the base agent and the curing agent is preferably 2 to 25 moles of isocyanate functional groups (-NCO) per mole of polyol hydroxyl groups (-OH). If the molar ratio (-NCO) / (-OH) is less than 2 and the amount of isocyanate functional groups (-NCO) is small, the curing reaction may not proceed sufficiently, and appropriate coating strength and heat resistance may not be obtained. On the other hand, if the molar ratio (-NCO) / (-OH) exceeds 25 and the amount of isocyanate functional groups (-NCO) is large, the reaction with functional groups other than the polyol may proceed too much, and the coating may become too hard and may not be able to obtain appropriate elongation. A particularly preferred molar ratio (-NCO) / (-OH) of polyol hydroxyl groups and isocyanate functional groups is 5 to 20.

[0066] The two-component curing polyester urethane resin preferably has the following physical properties in the cured film after the reaction. In order to ensure good moldability and interlayer bonding strength of the molded packaging material 1, the cured film preferably has a Young's modulus of 70 to 400 MPa as determined by a tensile test (JIS K7162). A particularly preferred Young's modulus is 100 to 300 MPa. The breaking strength is preferably 20 to 70 MPa and the breaking elongation is preferably 50 to 400%. A particularly preferred breaking strength is 30 to 50 MPa and a particularly preferred breaking elongation is 100 to 300%. Furthermore, it is preferred that the tensile stress-strain curve (SS curve) does not show a decrease in strength before breaking. FIG. 2 shows three patterns of SS curves. Pattern A has a small amount of strain relative to the tensile stress, and pattern B has a large amount of strain, but in both cases, the amount of strain increases with an increase in the tensile stress, and no decrease in strength before breaking is observed. On the other hand, pattern C shows a decrease in tensile stress as the amount of strain increases, and a decrease in strength before breaking is observed. In the present invention, it is preferable that the cured film of the two-component curing adhesive does not exhibit a decrease in strength in the SS curve, and more preferably, does not exhibit an inflection point where the strength changes suddenly in the SS curve.

[0067] The adhesive containing the two-component curing polyester urethane resin is prepared by polycondensing polyvalent carboxylic acid and polyhydric alcohol, which are the raw materials for the polyester resin, and, if necessary, further extending the chain with a polyfunctional isocyanate, and mixing with a solvent, a urethanization reaction catalyst, and various additives such as a coupling agent for improving adhesive strength, an epoxy resin, an antifoaming agent, a leveling agent, an ultraviolet absorber, and an antioxidant to form a fluid polyester resin solution, and then blending this with a polyfunctional isocyanate compound, which is a curing agent, or further with a solvent to prepare a low-viscosity fluid material.

[0068] The colored adhesive composition is prepared by mixing a colored pigment and an adhesive (including a solvent and various additives) containing the two-component curing polyester urethane resin prepared by the above-mentioned method in a predetermined ratio. The method of laminating the metal foil layer 4 and the heat-resistant resin layer 2 is not limited, but a method called dry lamination is recommended. Specifically, the colored adhesive composition prepared is applied to the upper surface of the metal foil layer 4 or the lower surface of the heat-resistant resin layer 2, or both surfaces, and the solvent is evaporated to form a dry film, and then the metal foil layer 4 and the heat-resistant resin layer 2 are laminated together. Then, the two-component curing polyester urethane resin is cured according to the curing conditions. As a result, the metal foil layer 4 and the heat-resistant resin layer 2 are bonded via the first adhesive layer 5. Examples of the method of applying the colored adhesive composition include gravure coating, reverse roll coating, and lip roll coating.

[0069] (Second adhesive layer) The second adhesive layer 6 is not particularly limited, and examples thereof include adhesive layers formed from polyurethane adhesives, acrylic adhesives, epoxy adhesives, polyolefin adhesives, elastomer adhesives, fluorine adhesives, acid-modified polypropylene adhesives, etc. Among these, it is preferable to use acrylic adhesives and polyolefin adhesives, and in this case, the electrolyte resistance and water vapor barrier properties of the packaging material 1 can be improved.

[0070] The method for bonding the metal foil layer 4 and the thermoplastic resin layer 3 is not limited, but an example of the method is a dry lamination method in which an adhesive constituting the second adhesive layer is applied and dried, and then the layers are bonded together, as in the case of bonding the metal foil layer 4 and the heat-resistant resin layer 2 described above.

[0071] (Production of molding packaging materials) A laminate is formed by bonding the heat-resistant resin layer 2 to the upper surface of the metal foil layer 4 via the above-mentioned first adhesive layer 5 (colored adhesive composition) and bonding the thermoplastic resin layer 3 to the lower surface via the second adhesive layer 6. By maintaining this laminate at a predetermined temperature according to the curing conditions of the two-component curing polyester urethane resin used, the heat-resistant resin layer 2 and the thermoplastic resin layer 3 are bonded to both sides of the metal foil layer 4 via the first adhesive layer 5 and the second adhesive layer 6, respectively, to produce the moldable packaging material 1.

[0072] The method and process for bonding the layers of the moldable packaging material of the present invention are not limited to the above-mentioned method and process, and packaging materials produced by other methods and processes are also included in the present invention.

[0073] [Other forms of molded packaging materials] The moldable packaging material of the present invention is not limited to the laminated structure shown in Fig. 1, and layers can be added to improve its functionality as a packaging material. The moldable packaging material 10 shown in Fig. 3 has chemical conversion coatings 11a, 11b formed on both sides of the metal foil layer 4. The moldable packaging material 20 shown in Fig. 4 has a matte coating layer 21 formed on the outer surface of the heat-resistant resin layer 2 in addition to the chemical conversion coatings 11a, 11b.

[0074] (Conversion coating on metal foil layer) The outer and inner layers of the molding packaging material are layers made of resin, and although only in very small amounts, there is a risk of light, oxygen, and liquid penetrating from the outside of the case, and there is a risk of contents (battery electrolyte, food, medicines, etc.) penetrating from the inside. If these intruders reach the metal foil layer, they will cause corrosion of the metal foil layer. In the molding packaging material of the present invention, highly corrosion-resistant chemical conversion coatings 11a, 11b are formed on the surface of metal foil layer 4, thereby improving the corrosion resistance of metal foil layer 4.

[0075] A chemical conversion coating is a coating formed by applying a chemical conversion treatment to the surface of a metal foil, and can be formed, for example, by applying a chromate treatment to the metal foil or a non-chromium type chemical conversion treatment using a zirconium compound. For example, in the case of chromate treatment, an aqueous solution of any one of the mixtures 1) to 3) below is applied to the surface of a degreased metal foil and then dried. 1) A mixture of phosphoric acid, chromic acid, and at least one of a metal salt of fluoride and a non-metal salt of fluoride. 2) A mixture of phosphoric acid, any one of an acrylic resin, a chitosan derivative resin, and a phenolic resin, and at least one of chromic acid and a chromium (III) salt. 3) A mixture of phosphoric acid, an acrylic resin, a chitosan derivative resin, or a phenolic resin, at least one of chromate and a chromium (III) salt, and at least one of a metal salt of fluoride and a nonmetal salt of fluoride. The chemical conversion coatings 11a and 11b have a chromium deposition amount of 0.1 to 50 mg / m 2 A chemical conversion coating having such a thickness or chromium coating amount can provide a highly corrosion-resistant moldable packaging material.

[0076] Although the moldable packaging material 10 in FIG. 3 is an example in which chemical conversion coatings 11a, 11b are formed on both sides of the metal foil layer 4, packaging materials having a chemical conversion coating on only one side are also included in the present invention.

[0077] (Matte coat layer) The matte coat layer 21 is formed on the outer surface of the heat-resistant resin layer 2, and is a layer that imparts good slipperiness to the surface of the moldable packaging material 20, thereby improving moldability.

[0078] The matte coat layer 21 is a matte coat layer made of a resin composition containing inorganic fine particles dispersed in a heat-resistant resin component. In particular, the matte coat layer 21 is preferably made of a resin composition containing a two-component curing type heat-resistant resin and 0.1% by mass to 1% by mass of inorganic fine particles having an average particle size of 1 μm to 10 μm.

[0079] Examples of the heat-resistant resin include acrylic resin, epoxy resin, polyester resin, urethane resin, polyolefin resin, and fluorine resin. In terms of excellent moldability, chemical resistance, solvent resistance, and scratch resistance, it is preferable to use a resin composition containing a base resin containing a phenoxy resin and a urethane resin and a curing agent, and the mass ratio of the phenoxy resin to the urethane resin in the base resin is 1:0.5 to 2:2. Furthermore, a two-component curing type heat-resistant resin in which the base resin is a polyol and the curing agent is a polyfunctional isocyanate can be used.

[0080] The inorganic fine particles are not particularly limited, but examples thereof include silica, alumina, calcium oxide, calcium carbonate, calcium sulfate, calcium silicate, and the like. Among these, it is preferable to use silica.

[0081] The matte coat layer 21 is formed by applying a matte coat composition containing the above-mentioned inorganic fine particles and a heat-resistant resin onto the surface of the heat-resistant resin layer 2 and curing it.

[0082] The thickness of the matte coat layer 21 after curing is preferably 0.5 to 5 μm. A layer thinner than the lower limit of the above range is less effective in improving slipperiness, while a layer thicker than the upper limit of the above range increases costs. A particularly preferred thickness is in the range of 1 to 3 μm.

[0083] The gloss value of the surface of the matte coat layer 21 is preferably set to 1% to 15% as measured at a 60° reflection angle based on JIS Z8741. The gloss value is obtained by measuring at a 60° reflection angle using, for example, a gloss meter "micro-TRI-gloss-s" manufactured by BYK.

[0084] The step of forming the matte coat layer 21 can be carried out at any time after the heat-resistant resin layer 2 is bonded to the metal foil layer 4 via the first adhesive layer 5. The matte coat layer 21 can be formed after the heat-resistant resin layer 2 is bonded and before the thermoplastic resin layer 3 is bonded, or the matte coat layer 21 can be formed after the heat-resistant resin layer 2 and the thermoplastic resin layer 3 are bonded to the metal foil layer 4.

[0085] Although the moldable packaging material 20 in FIG. 4 shows an example in which both the chemical conversion coatings 11a, 11b and the matte coating layer 21 are added to the basic structure in FIG. 1, it is not necessary to have all of these at the same time, and a packaging material in which only the matte coating layer 21 is added to the basic structure in FIG. 1 is also included in the present invention.

[0086] [Molded case] A molded case (battery case, etc.) can be obtained by molding (deep drawing, stretch molding, etc.) the moldable packaging materials 1, 10, and 20 of the present invention. EXAMPLES

[0087] Next, specific examples of the present invention will be described, but the present invention is not limited to these examples. [Production of molding packaging material] In the following Examples 1 to 5 and Comparative Examples 1 to 5, moldable packaging materials 20 having the laminated structure shown in Fig. 4 were produced. These differ only in the color pigment concentration in the color adhesive composition constituting the first adhesive layer 5, the coating amount of the color adhesive composition, the color pigment content in the first adhesive layer, and the heat-resistant resin layer 2, and the other materials are common to all of them. The common materials are as follows:

[0088] The metal foil layer 4 is an aluminum foil 4 made of A8079 having a thickness of 40 μm. A chemical conversion treatment solution consisting of polyacrylic acid, a trivalent chromium compound, water, and alcohol was applied to both sides of this aluminum foil, and the coatings 11a and 11b were formed by drying at 150° C. The amount of chromium deposited by the chemical conversion coatings 11a and 11b was 10 mg / m 2 It is.

[0089] The thermoplastic resin layer 3, which is the inner layer, is an unstretched polypropylene film having a thickness of 40 μm.

[0090] For the second adhesive layer 6, a polyacrylic adhesive was used. (First adhesive layer) The colored adhesive composition constituting the first adhesive layer 5 was prepared by the following method using carbon black as the color pigment and a two-component curing polyester urethane resin as the adhesive.

[0091] First, a polyester resin (polyester polyol) which is the main component of the two-component curing polyester urethane resin is prepared. The main component is prepared by melting 30 mol parts of neopentyl glycol, 30 mol parts of ethylene glycol, and 40 mol parts of 1,6-hexanediol at 80°C, and then condensing and polymerizing 30 mol parts of adipic acid (methylene number 4) which is an aliphatic dicarboxylic acid, and 70 mol parts of isophthalic acid which is an aromatic dicarboxylic acid at 210°C for 20 hours while stirring to obtain a polyester polyol. This polyester polyol has a number average molecular weight (Mn) of 12,000, a weight average molecular weight (Mw) of 20,500, and a ratio (Mw / Mn) of these of 1.71. Furthermore, 60 mol parts of ethyl acetate was added to 40 mol parts of this polyester polyol to obtain a fluid polyester polyol resin solution. The hydroxyl value was 2.2 mgKOH / g (solution value).

[0092] Next, 100 parts by mass of the polyester polyol resin solution and 64.4 parts by mass of ethyl acetate were mixed with the required amount of carbon black having an average particle diameter of 1.0 μm, and the carbon black pigment was dispersed using a pigment disperser to obtain a base material containing a coloring pigment in which the carbon black concentration relative to the solid component (total of polyester polyol and carbon black) was adjusted to the concentration shown in Table 1. Then, 7.1 parts by mass of an adduct between tolylene diisocyanate (TDI) (aromatic type) which is an aromatic isocyanate compound and trimethylolpropane (NCO% 13.0%, solid content 75%) was mixed as a curing agent relative to 100 parts by mass of the base material containing the coloring pigment, and 34.1 parts by mass of ethyl acetate were further mixed and thoroughly stirred to obtain a coloring adhesive composition. In the coloring adhesive composition, the molar ratio (-NCO) / (-OH) of the isocyanate functional group (-NCO) to the polyester polyol hydroxyl group (-OH) was 10.

[0093] A cured film of the two-component curing polyester urethane resin adhesive, that is, a cured film having a composition in which the coloring pigment is excluded from the composition of the first adhesive layer, was prepared and its physical properties were evaluated.

[0094] A two-component curing polyester urethane resin adhesive was applied to a non-adhesive untreated PP film so that the thickness after drying was 50 μm, and after the solvent was dried, the adhesive was cured by aging at 60° C. until the residual isocyanate was 5% or less. The cured film was peeled off from the untreated PP film and cut into a width of 15 mm to prepare a test piece.

[0095] The test pieces were subjected to a tensile test under the conditions of a gauge length of 50 mm and a tensile speed of 200 mm / min, and the Young's modulus, breaking strength and breaking elongation were measured, which were 140 MPa, 48 MPa and 217%. The SS curve in this tensile test was obtained, and the pattern was pattern A shown in Figure 2. (Heat-resistant resin layer) In Examples 1 to 4 and Comparative Example 5, a biaxially oriented nylon film having a thickness of 25 μm and a hot water shrinkage rate of 4.0% was used, and in Example 5 and Comparative Examples 1 to 4, a biaxially oriented nylon film having a thickness of 25 μm and a hot water shrinkage rate of 1.5% was used (see Table 1). The hot water shrinkage rate was measured by the method described above. (Laminating each layer) A predetermined amount of colored adhesive composition was applied to one surface of the aluminum foil 4 on which the chemical conversion films 11a and 11b were formed, and dried to form a first adhesive layer 5. The composition and application amount (weight after drying) of the colored adhesive composition for each example are shown in Table 1, as well as the carbon black content in the first adhesive layer 5 and the film thickness of the first adhesive layer 5 after drying, which were calculated from these, are also shown in Table 1. Then, a heat-resistant resin layer 2 was attached to the first adhesive layer 5.

[0096] Next, a polyacrylic adhesive was applied to the other surface of the aluminum foil as a second adhesive layer 6, and a thermoplastic resin layer 3 was attached thereto.

[0097] A matte coat composition was prepared by mixing 80 parts by mass of fluoroethylene vinyl ester as a heat-resistant resin, 10 parts by mass of barium sulfate as inorganic fine particles, and 10 parts by mass of powdered silica for the matte coat layer 21. This matte coat composition was applied to the heat-resistant resin layer 2 so that the thickness after drying was 2 μm.

[0098] Furthermore, this laminate was aged in an environment of 40° C. for 5 days to obtain a moldable packaging material 20 shown in FIG. [Evaluation of molding packaging materials] Each of the moldable packaging materials obtained as described above was evaluated according to the following evaluation methods. The results are shown in Table 1. (Concealment) The molding packaging material 20 was visually observed from the heat-resistant resin layer 2 side, and those in which the metal foil layer 4 was not visible were rated as "concealable: ◯", and those in which the metal foil layer 4 was visible were rated as "no concealment: ×". (Whether or not peeling occurs) Thirty pieces of the moldable packaging material 20 were manufactured for each of the examples and comparative examples. Each moldable packaging material 20 was subjected to deep drawing using a punch and a die or the like in a manner in which the inner thermoplastic resin layer 3 was brought into contact with the punch to form a convex portion 31 having a length of 33 mm, a width of 54 mm, and a depth of 4.0 mm, to produce a test material 30 having a shape having a flat flange around the convex portion 31 (see FIG. 5).

[0099] The top surface 32 of the protrusion 31 of the test material 30 was crushed, and the crushed test material 30 was subjected to a high temperature and humidity test and a hot water immersion test to check for peeling of the heat-resistant resin layer 2. In the high temperature and humidity test, the crushed test material 30 was kept in an atmosphere of a temperature of 70°C and a humidity of 90% for two weeks. In the hot water immersion test, the crushed test material 30 was immersed in hot water of 45°C and kept for two weeks.

[0100] In both tests, the 30 test pieces 30 were visually observed after the test, and the number of test pieces 30 in which the heat-resistant resin layer 2 had peeled off from the metal foil layer 4 was judged according to the following criteria.

[0101] ◎:0 pieces 〇:1~2 pieces △:3~5 pieces ×: 6~30 pieces (Curl characteristics) The moldable packaging materials 20 produced in the above Examples 1 to 5 and Comparative Examples 1 to 5 were cut into blanks of 100 mm x 100 mm to prepare test materials. Next, these test materials were placed on a horizontal table with the matte coat layer 21 facing up, and the height of the curl was measured and evaluated according to the following criteria.

[0102] ○: 0~20mm ×: More than 20mm (Molding height) Using a depth-free straight mold, one-stage deep drawing was performed on the molded packaging material under the following molding conditions, and the moldability was evaluated for each molding depth (9.0mm, 8.5mm, 8.0mm, 7.5mm, 7.0mm, 6.5mm, 6.0mm, 5.5mm, 5.0mm, 4.5mm, 4.0mm). The maximum molding depth (mm) at which good molding without any pinholes or cracks could be performed at the corners was investigated, and the moldability was evaluated based on the following criteria. Products with ratings of ◎ and ◯ are acceptable. The presence or absence of pinholes was checked by visually observing the presence or absence of transmitted light passing through the pinholes. Molding conditions Mold: Punch: 33mm x 54mm, Die: 80mm x 120mm, Corner R: 2mm, Punch R: 1.3mm, Die R: 1mm Judgment criteria The maximum forming depth without pinholes or cracks is ◎: 7.0mm or more ○: 6.0mm or more and less than 7.0mm △: Over 5.0mm and under 6.0mm ×: 5.0mm or less (comprehensive evaluation) Based on five tests, namely hiding power, high temperature and humidity test, warm water immersion test, curl characteristics, and molding height, the product was comprehensively evaluated according to the following criteria.

[0103] ◎: There are two or more ◎ and no ×.

[0104] 〇: One ◎ and no × ×: × or △

[0105] [Table 1]

[0106] It was confirmed from Table 1 that in Examples 1 to 5, the heat-resistant resin layer did not peel off even under harsh environments, the hiding power was obtained by the color pigment, curling was resistant, and moldability was excellent. [Industrial Applicability]

[0107] The moldable packaging material according to the present invention is suitable for use as a case for batteries such as notebook computers, mobile phones, in-vehicle batteries, and stationary lithium ion polymer secondary batteries, and is also suitable for use as a packaging material for food and medicine, although it is not limited to these applications. Among these, it is particularly suitable for use as a battery case. [Explanation of symbols]

[0108] 1, 10, 20…Molding packaging material 2...Heat-resistant resin layer (outer layer) 3...Thermoplastic resin layer (inner layer) 4...Metal foil layer (aluminum foil) 5...First adhesive layer (colored adhesive composition) 6…Second adhesive layer 11a, 11b...chemical conversion coating 21…Matte coat layer

Claims

1. a heat-resistant resin layer as an outer layer, a thermoplastic resin layer as an inner layer, a metal foil layer disposed between these two layers, and a first adhesive layer disposed between the metal foil layer and the heat-resistant resin layer; A moldable packaging material comprising a second adhesive layer disposed between the metal foil layer and the thermoplastic resin layer, The first adhesive layer is made of a colored adhesive composition containing a color pigment and an adhesive, the colored adhesive composition contains a color pigment in an amount of 2% by mass or more and less than 5% by mass based on the solid content, and the first adhesive layer has a thickness of 5 g / m 2 ~10g / m 2 The first adhesive layer is coated with a colored adhesive composition of 0.25 g / m 2 ~0.49g / m 2 Contains a color pigment of A moldable packaging material, characterized in that the color pigment is carbon black.

2. The adhesive in the colored adhesive composition contains a two-component curing type polyester urethane resin containing a polyester resin as a base resin and a polyfunctional isocyanate compound as a curing agent, The molded packaging material according to claim 1, characterized in that the polyester resin has a number average molecular weight (Mn) of 8,000 to 25,000, a weight average molecular weight (Mw) of 15,000 to 50,000, and a ratio thereof (Mw / Mn) of 1.3 to 2.5, and the polyfunctional isocyanate compound contains 50 mol % or more of aromatic isocyanate.

3. In the two-component curing polyester urethane resin, the polyester resin as a base material is made from dicarboxylic acid and dialcohol as raw materials, The moldable packaging material according to claim 2, wherein the dicarboxylic acid includes an aliphatic dicarboxylic acid having an even number of methylene chains and an aromatic dicarboxylic acid, and the content of the aromatic dicarboxylic acid relative to the total amount of the aliphatic dicarboxylic acid and the aromatic dicarboxylic acid is 40 to 80 mol %.

4. 4. The moldable packaging material according to claim 2, wherein the cured film of the two-component curing polyester urethane resin has a Young's modulus of 70 to 400 MPa as determined by a tensile test (JIS K7162).

5. 5. The moldable packaging material according to claim 1, wherein the first adhesive layer has a thickness of 4.5 μm to 10 μm.

6. 6. The moldable packaging material according to claim 1, further comprising a chemical conversion coating on at least one surface of the metal foil layer.

7. 7. The moldable packaging material according to claim 1, wherein the heat-resistant resin layer is made of a stretched film having a hot water shrinkage rate of 2% to 20%.

8. 8. The moldable packaging material according to claim 1, further comprising a matte coating layer on an outer surface of the heat-resistant resin layer.

9. A molded case, which is obtained by deep drawing or stretch molding the moldable packaging material according to any one of claims 1 to 8.

10. The molded case according to claim 9, which is used as a battery case.

Citation Information

Patent Citations

  • Laminated aluminum material for electrolytic-capacitor case use

    JP1992127413A

  • Packaging material for electrochemical cell

    JP2011054563A

  • Nonaqueous electrolyte battery

    JP2011096552A

  • Packaging material for electrochemical cell

    JP2013016513A

  • Packaging material for electrochemical cell

    JP2013152907A